2022
DOI: 10.5230/jgc.2022.22.e12
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Survival of Gastric Cancer Patients With Distant Lymph Node Metastasis Using Prealbumin Level and Prothrombin Time: Contour Plots Based on Random Survival Forest Algorithm on High-Dimensionality Clinical and Laboratory Datasets

Abstract: Purpose This study aimed to identify prognostic factors for patients with distant lymph node-involved gastric cancer (GC) using a machine learning algorithm, a method that offers considerable advantages and new prospects for high-dimensional biomedical data exploration. Materials and Methods This study employed 79 features of clinical pathology, laboratory tests, and therapeutic details from 289 GC patients whose distant lymphadenopathy was presented as the first episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Since most components of the coagulation system were synthesized in the liver, the coagulation state of patients was also closely related to liver function [ 38 ]. Many studies have found that coagulation status could reflect the clinical outcomes of various cancers, and PT and TT were both prognostic indicators for HCC patients in this study [ 39 41 ]. Although PT was the most important indicator for detecting the coagulation status of patients, it was influenced by various factors such as liver synthesis function and inflammatory factors [ 42 ].…”
Section: Discussionmentioning
confidence: 68%
“…Since most components of the coagulation system were synthesized in the liver, the coagulation state of patients was also closely related to liver function [ 38 ]. Many studies have found that coagulation status could reflect the clinical outcomes of various cancers, and PT and TT were both prognostic indicators for HCC patients in this study [ 39 41 ]. Although PT was the most important indicator for detecting the coagulation status of patients, it was influenced by various factors such as liver synthesis function and inflammatory factors [ 42 ].…”
Section: Discussionmentioning
confidence: 68%
“…LNM is the most important factor for the overall survival of gastric cancer patients following curative gastrectomy, and the increased number of metastatic lymph nodes often indicates a decrease in survival rates [ 4 7 ]. Metastasis to lymph nodes also leads to the subsequent metastasis to other organs and the development of cancer [ 8 10 ], and illuminating the mechanisms underlying LNM is an urgent problem to solve.…”
Section: Introductionmentioning
confidence: 99%